2023
DOI: 10.3389/fendo.2023.1096105
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal anti-vascular endothelial growth factor, laser photocoagulation, or combined therapy for diabetic macular edema: A systematic review and network meta-analysis

Abstract: PurposeTo conduct a network meta-analysis (NMA) comparing the efficacy of anti-vascular endothelial growth factor (VEGF) therapy alone versus laser photocoagulation (LP) therapy alone or anti-VEGF therapy combined with LP therapy for diabetic macular edema (DME).MethodsPubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Trials were systematically searched for studies comparing anti-VEGF therapy alone versus LP therapy alone or anti-VEGF therapy combined with LP therapy for DME. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…DME is a common complication of diabetic retinopathy and a leading cause of vision loss. Its current first-line treatment involves IV injections of anti-VEGF agents (Ranibizumab, Aflibercept, and Bevacizumab), which have shown significant efficacy in improving vision [ 101 ]. However, these treatments have limitations, including the need for frequent injections and potential AEs related to the IV application.…”
Section: Suprachoroidal Injection In Ocular Diseasesmentioning
confidence: 99%
“…DME is a common complication of diabetic retinopathy and a leading cause of vision loss. Its current first-line treatment involves IV injections of anti-VEGF agents (Ranibizumab, Aflibercept, and Bevacizumab), which have shown significant efficacy in improving vision [ 101 ]. However, these treatments have limitations, including the need for frequent injections and potential AEs related to the IV application.…”
Section: Suprachoroidal Injection In Ocular Diseasesmentioning
confidence: 99%
“…In comparison, laser treatment is generally considered more cost-effective than pharmacotherapy, including both anti-VEGF and steroid treatments [ 94 ]. Laser treatment also offers the advantage of a longer-lasting effect compared to anti-VEGF therapy [ 95 ]. Moreover, several studies have demonstrated that the combination of laser photocoagulation with anti-VEGF treatment has the potential to reduce the frequency of injections ( Table 2 ) [ 96 ].…”
Section: The Current Role Of Laser Photocoagulation In the Era Of Int...mentioning
confidence: 99%